2013
DOI: 10.3390/s130809549
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Different Error Modeling of MEMS Applied to GPS/INS Integrated Systems

Abstract: Advances in the development of micro-electromechanical systems (MEMS) have made possible the fabrication of cheap and small dimension accelerometers and gyroscopes, which are being used in many applications where the global positioning system (GPS) and the inertial navigation system (INS) integration is carried out, i.e., identifying track defects, terrestrial and pedestrian navigation, unmanned aerial vehicles (UAVs), stabilization of many platforms, etc. Although these MEMS sensors are low-cost, they present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 23 publications
0
109
0
4
Order By: Relevance
“…However, it is difficult to remove the stochastic error easily by any physical method, while a precise mathematical model can solve the problem far more effectively. Although a first-order Gauss-Markov model can accurately build a stochastic model for navigation-grade INS systems, low-cost INS systems need a more precise stochastic model to ensure precision of the navigation solution because of the complex noise components existing in it [39]. The autocorrelation results ( Figure 9) from the sensor stochastic error calculations show that the errors cannot be simply modeled by a first-order Gauss-Markov model.…”
Section: Stochastic Error Modelmentioning
confidence: 99%
“…However, it is difficult to remove the stochastic error easily by any physical method, while a precise mathematical model can solve the problem far more effectively. Although a first-order Gauss-Markov model can accurately build a stochastic model for navigation-grade INS systems, low-cost INS systems need a more precise stochastic model to ensure precision of the navigation solution because of the complex noise components existing in it [39]. The autocorrelation results ( Figure 9) from the sensor stochastic error calculations show that the errors cannot be simply modeled by a first-order Gauss-Markov model.…”
Section: Stochastic Error Modelmentioning
confidence: 99%
“…Additionally, the research on MEMS sensors has shown that the errors in their measurements are a combination of random error sources, non linearities and thermally induced alterations. A global analysis on the model of errors in MEMS accelerometers can be found in (11) , while a more detailed modeling of their measurement noise is reported in (12) , where the use of Allan's variance is clearly described. Finally, a comprehensive analysis on the bias in the measurements has been conducted in (13) .…”
Section: Kalman Estimator Utilizing a Mems Accelerometermentioning
confidence: 99%
“…The calibration procedure can characterize and then delete the systematic errors from raw measurements [12] [13] [14]. To remove the systematic error, it is necessary to compare the raw data of IMU with a known reference and then determine the systematic errors which agree with that reference.…”
Section: Calibration Of Systematic Errorsmentioning
confidence: 99%